ROLES OF MELTING AND METASOMATISM IN THE FORMATION OF THE LITHOSPHERIC MANTLE BENEATH THE LEIZHOU PENINSULA, SOUTH CHINA - Yu J.-H.; Xu X.; O'Reilly S.Y.; Zhang M.; Griffin W.L. (My University, 2006)
This study characterizes the nature of fluid interaction and melting processes in the lithospheric mantle beneath the Yingfengling and Tianyang volcanoes, Leizhou Peninsula, South China, using in situ trace-element analyses of clinopyroxene, amphibole and garnet from a suite of mantle-derived xenoliths. Clinopyroxenes from discrete spinel lherzolites exhibit large compositional variations ranging from extremely light rare earth element (LREE)-depleted to LREE-enriched. Trace-element modelling for depleted samples indicates that the Leizhou lherzolites are the residues of a mantle peridotite source after extraction of ~1-11% melt generated by incremental melting in the spinel lherzolite field with the degree of melting increasing upwards from about 60km to 30km. This process is consistent with gradational melting at different depths in an upwelling asthenospheric column that subsequently cooled to form the current lithospheric mantle in this region. The calculated melt production rate of this column could generate mafic crust 5-6km thick, which would account for most of the present-day lower crust. The formation of the lithospheric column is inferred to be related to Mesozoic lithosphere thinning. Al-augite pyroxenites occur in composite xenoliths; these are geochemically similar to HIMU-type ocean island basalt. These pyroxenites postdate the lithospheric column formation and belong to two episodes of magmatism. Early magmatism (forming metapyroxenites) is inferred to have occurred during the opening of the South China Sea Basin (32-15Ma), whereas the most recent magmatic episode (producing pyroxenites with igneous microstructures) occurred shortly before the eruption of the host magmas (6-0.3-Ma). Trace-element traverses from the contacts of the Al-augite pyroxenite with the spinel peridotite wall-rock in composite xenoliths record gradients in the strength and nature of metasomatic effects away from the contact, showing that equilibrium was not attained. Significant enrichment in highly incompatible elements close to the contacts, with only slight enrichment in Sr, LREE and Nb away from the contact, is inferred to reflect the different diffusion rates of specific trace elements. The observed geochemical gradients in metasomatic zones show that Sr, La, Ce and Nb have the highest diffusion rates, other REE are intermediate, and Zr, Hf and Ti have the lowest diffusion rates. Lower diffusion rates observed for Nb, Zr, Hf and Ti compared with REE may cause high field strength element (HFSE) negative anomalies in metasomatized peridotites. Therefore, metasomatized lherzolites with HFSE negative anomalies do not necessarily require a carbonatitic metasomatizing agent. © The Author 2005. Published by Oxford University Press. All rights reserved.
Keywords: CHINA; CLINOPYROXENE TRACE ELEMENTS; LITHOSPHERE; MANTLE METASOMATISM; MANTLE PARTIAL MELTING; MANTLE XENOLITHS; TRACE-ELEMENT DIFFUSION RATES